Inggris - Nur Ikhsan; Ellyana Ilsan Eka Putri (Character Jurnal Penelitian Psikologi, 2026)
The rapid advances in information technology have made the internet a primary tool in academia, which has also led to the emergence of cyberloafing as a way for students to escape academic pressure. This study aims to examine the influence of academic stress on cyberloafing behavior among college students at University X. The study used a non-experimental quantitative method with an associative-predictive approach, involving 200 respondents selected via accidental sampling. The instruments used were the modified Student Cyberloafing Scale and the Educational Stress Scale for Adolescents (ESSA). The results indicate a positive and significant effect of academic stress on cyberloafing behavior, with a significance level of p < 0.001 and a regression coefficient of 0.811. Analysis of the coefficient of determination shows that academic stress accounts for 36.5% of the variance in cyberloafing behavior, while the remainder is influenced by other factors outside the scope of this study. These findings emphasize the importance of interactive learning methods and counseling services to develop better coping strategies to reduce non-academic internet use during learning activities. Abstrak Pesatnya kemajuan teknologi informasi menjadikan internet sarana utama dalam bidang akademik. Namun, kondisi ini juga memicu munculnya fenomena cyberloafing sebagai bentuk pengalihan mahasiswa dari tekanan akademik. Penelitian ini bertujuan untuk mengetahui pengaruh stres akademik terhadap perilaku cyberloafing pada mahasiswa Universitas X. Metode yang digunakan adalah kuantitatif non-eksperimen dengan pendekatan asosiatif prediktif, melibatkan 200 responden yang diperoleh melalui teknik accidental sampling. Instrumen yang digunakan adalah Student Cyberloafing Scale dan Educational Stress Scale for Adolescents (ESSA) yang telah dimodifikasi. Hasil penelitian menunjukkan adanya pengaruh positif dan signifikan stres akademik terhadap perilaku cyberloafing dengan nilai signifikansi p < 0,001 dan koefisien regresi sebesar 0,811. Analisis koefisien determinasi menunjukkan stres akademik mampu menjelaskan 36,5% varian perilaku cyberloafing, sementara sisanya dipengaruhi oleh faktor lain di luar penelitian ini. Temuan ini menekankan pentingnya metode pembelajaran interaktif dan layanan konseling untuk mengembangkan strategi coping yang lebih baik guna mengurangi penggunaan internet non-akademik selama kegiatan belajar.